Shallow Seismic Reflection Profiling of Waste Disposal Sites - Boyce, Joseph; Koseoglu, Berkant (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary Conventional approaches to environmental site characterization usually involve drilling of relatively dense networks of continuously sampled and geophysically logged bore holes. Inglaciated terrains, problems are often encountered in determining the lateral continuity and three-dimensional sub-surface geometry of sediments between bore hole locations. An improved and potentially more cost-effective approach combines drilling and bore hole sampling with high-resolution shallow seismic reflection profiling. This approach is illustrated with case studies from candidate landfill sites. Seismic data provide critical information regarding the lateral continuity and geometry of sediments and pathways for groundwater and contaminants.